An uncommon use of irradiated flavins: Brønsted acid catalysis. Issue 42 (21st April 2020) - Arakawa, Yukihiro; Mihara, Tomohiro; Fujii, Hiroki; Minagawa, Keiji; Imada, Yasushi
Abstract : Visible light irradiation to flavins in the presence of thiols and O2 provides Brønsted acidic species that can be used as efficient catalysts for thioacetalizations and for Mannich-type reactions under non-irradiation and mild conditions. Abstract : We present that thioacetalization of aldehydes can be induced by blue light irradiation in the presence of a catalytic amount of riboflavin tetraacetate (RFTA) under aerobic conditions. Several control experiments have suggested that the reaction is more likely to be catalyzed by acidic species generated in situ upon light irradiation. We have proposed that single electron transfer from a thiol (RSH) to the excited state of RFTA can take place to give a one-electron oxidized thiol (RSH + ˙) and the one-electron reduced RFTA (RFTA − ˙), which can be trapped by molecular oxygen to be stabilized as Brønsted acids including the protonated RFTA − ˙ (RFTAH˙). Finally, we have demonstrated that such acidic species can be prepared in advance as a solution and used as Brønsted acid catalysts for not only thioacetalization but also Mannich-type reactions.